High-grade squamous intraepithelial cervical lesions regression in pregnant women - Campos Siccha, Gerardo (2014)
Objectives: To determine high-grade intraepithelial cervical lesions colposcopic regression in pregnant women. Design: Cross-sectional observational study. Setting: Hospital Nacional Docente Madre Niño San Bartolome, Lima, Peru. Participants: Pregnant women with high grade intraepithelial cervical lesion diagnosis – HSIL (CIN II, CIN III, cancer in situ). Interventions: Results of HSIL in Papanicolaou cytology reports from 2004 until 2008 were searched in Pathology Service software.. Main outcome measures: Colposcopic regression of high degree lesions in puerperal women. Results: HSIL distribution was statistically different between Papanicolaou and colposcopy reports but both maintained CIN II, CIN III and cancer in situ order. According to colposcopy HSIL was more frequent than CIN II (83.3%) and cancer in situ followed by CIN III and cancer in situ (15% and 1.7% respectively). In post partum control 38.3% had normal colposcopy and 61.7% of cases remained pathological but presented improvement to low-risk lesions such as CIN I (26.7%). Only 35% persisted as high-risk lesions (CIN II, CIN III, cancer in situ: 25%, 6.7% and 3.3% respectively). These post partum changes were statistically significant. Birth by vaginal delivery was related to lower persistence of high risk lesions in the post partum compared to birth by caesarean section. Thirty-six and older women showed improvement in the post partum as well as those having a single sexual partner and beginning sexual relations after age 20. Conclusions: Post partum spontaneous regression of high degree cervical lesions occurred in 65% of puerperal women, more in those with vaginal delivery, 36 year-old or older, history of one sexual partner and beginning sexual relations after age 20.